Making Scenes : Reggae, Punk, and Death Metal in 1990s Bali - Baulch, Emma, 1968- (Book collections on Project MUSE., 2007)
An ethnographic exploration of identity politics in three of Bali s musical subcultures-reggae, punk, and death metal-during the 1990s.